CONTROL OF THE ADMINISTRATIVE FUNCTIONS APPLIED IN A COMPANY - Hernández, Victoria Salgado (IJRDO - Journal of Business Management, 2022)
Companies have been a fundamental part for the economic growth of many places, but as these companies can become efficient and profitable before the great market competition that is had in these times, this is due to the administration with which it is counted, the managers of the companies play an important role for the development and growth of the companies, since they are the ones who are responsible for delegating each of the activities when carrying out in this same, as well as the decision making that best suits the company to have its own benefits. This is where the administrative functions come in which seek to improve the performance of activities either in the short or long term. In this research it will be briefly described how this type of functions helps managers to be able to generate more confidence in their staff, to have a better performance in their activities but above all to how to generate greater profitability within the company.